Radar techniques using array antennas - Wirth, Wulf-Dieter (IET radar, sonar, navigation and avionics series, 2013)
"An updated version of the book published in 2001, this second edition includes new material on compressed sensing and its possible application to beam forming, results for phase-only-nulling against jammers, descriptions of further algorithms for superresolution and the reconnaissance of other radiating sources. This book also features a new chapter on radar operation by passive coherent location and the extension and explanation of the basic ideas for MIMO-radar. In addition to the coverage of antennas, array signal processing, adaptive digital beamforming and adaptive monopulse, several modern systems are described including space-time adaptive processing (STAP), moving target detection using synthetic aperture radar (SAR) and several other experimental phased array radar systems."--Publisher's description.